The Efficacy and Safety of Anti-TNF? Treatment in Ankylosing Spondylitis Patients with Late Onset Compared to Those with Adult Onset; The Data from TURKBIO Registry - Uslu, Sadettin; Can, Gercek; Cefle, Ayse; Yilmaz, Sema; Kocaer, Sinem Burcu; Inel, Tuba Yuce; Onen, Fatos (Wiley, 2019)
[Abstract Not Available]
Annual Meeting of the American-College-of-Rheumatology/Association-of-Rheumatology-Professionals (ACR/ARP) -- NOV 08-13, 2019 -- Atlanta, GA